2016
DOI: 10.1007/978-3-319-35135-3_23
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Functions of PACAP in the Placenta

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) is an endogenous neuropeptide with a widespread distribution both in the nervous system and peripheral organs. The peptide is also present in the female gonadal system, indicating its role in reproductive functions. While a lot of data are known on PACAP-induced effects in oogenesis and in the regulation of gonadotropin secretion at pituitary level, its placental effects are somewhat neglected in spite of the documented implantation deficit in mice lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 68 publications
0
9
0
1
Order By: Relevance
“…PACAPdeficient mice have been described to have impaired implantation (Isaac & Sherwood 2008), which, together with the increased rate of early postnatal death also leads to a reduced number of offspring (Gray et al 2001, Wilson & Cumming 2008. As PACAP is involved in several other processes, such as gametogenesis (Apa et al 2002, Li et al 2004, Barberi et al 2007, Koppan et al 2012, Canipari et al 2016, placental development (Horvath et al 2014(Horvath et al , 2016 and gonadotropin regulation (Kanasaki et al 2016), it can be hypothesized that lack of PACAP may also influence reproduction in germ cells (Lacombe et al 2006). In a previous study, we found that the diameter of sperm heads in PACAP-deficient mice was smaller, (Brubel et al 2012), but no data were obtained as to whether this resulted in abnormal motility.…”
Section: Introductionmentioning
confidence: 99%
“…PACAPdeficient mice have been described to have impaired implantation (Isaac & Sherwood 2008), which, together with the increased rate of early postnatal death also leads to a reduced number of offspring (Gray et al 2001, Wilson & Cumming 2008. As PACAP is involved in several other processes, such as gametogenesis (Apa et al 2002, Li et al 2004, Barberi et al 2007, Koppan et al 2012, Canipari et al 2016, placental development (Horvath et al 2014(Horvath et al , 2016 and gonadotropin regulation (Kanasaki et al 2016), it can be hypothesized that lack of PACAP may also influence reproduction in germ cells (Lacombe et al 2006). In a previous study, we found that the diameter of sperm heads in PACAP-deficient mice was smaller, (Brubel et al 2012), but no data were obtained as to whether this resulted in abnormal motility.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased mating behavior 9 and impaired implantation 10 as well as disturbed maternal behavior 9 and increased postnatal mortality with altered perinatal neurobehavioral development 11,12 in PACAP knockout mice have been suggested to account for the decreased number of offspring. For example, PACAP plays a role in fertilization, 13 influences trophoblast cell growth, migration, and placental functions 14 and plays a role in the blood flow of the uteroplacental unit. For example, PACAP plays a role in fertilization, 13 influences trophoblast cell growth, migration, and placental functions 14 and plays a role in the blood flow of the uteroplacental unit.…”
Section: Introductionmentioning
confidence: 99%
“…Several other effects of PACAP in reproductive functions have been suggested to play a role in the decreased reproductive rate described by several research groups. For example, PACAP plays a role in fertilization, 13 influences trophoblast cell growth, migration, and placental functions 14 and plays a role in the blood flow of the uteroplacental unit. 15 PACAP is a known modulator of innate and adaptive immune response.…”
Section: Introductionmentioning
confidence: 99%
“…This was the case in choriocarcinoma cells, where PACAP treatment led to further decrease in survival in cells exposed to hydrogen peroxide-induced oxidative stress or chemically induced in vitro hypoxia ( 113 ). However, no effect was observed in lipopolysaccharide-, ethanol or methotrexate-treated cells ( 113 , 114 ). Furthermore, in JAR choriocarcinoma cells, PACAP influenced the expression of several signaling molecules, such as ERK1/2, JNK, Akt, GSK, Bax, p38 MAPK ( 113 ).…”
Section: Pacap In the Uterus And Placentamentioning
confidence: 89%